SEVERAL ASPECTS OF DILTIAZEM AND ORGANIC NITRATES USAGE IN VARIOUS SEVERITY STABLE ANGINA PATIENTS - E. K. Butina; E. V. Bochkareva; N. A. Pozdnyakova (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To estimate the effectiveness of Diltiazem (Dlt) and its combination with nitrates in patients with ischemic heart disease (CHD) and arterial hypertension (AH) according to exercise tolerance by functional class (FC) of stable angina (StA).Material and methods. 30 CHD male patients at the age of 58,8±7,5 with StA II FC (n=11), III FC (n=19) and 1–2 stage AH were included into open randomized placebo-controlled study. Drug therapy: Dlt 90–180 mg bid, isosorbide 5-mononitrate 50 mg qd, trinitrolong 2 mg bid or tid. Effectiveness of the regular drug intake was controlled by repeated exercise tolerance tests (ETT) by treadmill with the value of threshold effort time (ThT). Total duration of treatment was 4 weeks.Results. At the beginning the ThT was 249,8±23,4 s for III FC and 368,6±14,4 s for II FC patients (p=0,0001). One dose of Dlt increased ThT in 5 hours to 387,3±37,5 s and 533,7±20,3 s in both groups, respectively (p=0,001), with the difference between groups being held. During regular Dlt intake the ThT in III FC angina patients reached 441,1±26,8 s, but in II FC patients in has not changed: 526,1±22,0 s. Additional nitrate intake to III FC group led to even more increase of ThT; in II FC patients there was no improvement. Combination therapy by Dlt and nitrates has not led to differences between III and II FC groups by achieved exercise tolerance. Hemodynamic parameters in both groups has not differ.Conclusion. For patients with III FC stable angina it is recommended to prescribe Dlt with nitrates because of additional effectiveness of combination that might be linked to the influence on cardiac hemodynamics and to improvement of myocardium metabolism. In II FC stable angina Dlt alone reaches its maximum antiischemic effect so the addition of nitrates is not helpful.